Utilization of solar thermal energy as a supplier of electric car batteries in indonesia - Ambia, Yahya Chairil; Fayisa, Fadhil; Rahmah, Ainun Nur; Alfian, Aghista; Ahmadi, Arga Farid (Universitas Negeri Semarang, 2024)
Utilizing solar thermal energy as an energy source to supply electric car batteries in Indonesia is a big solution for reducing carbon gas emissions and the use of fossil fuels. This research aims to provide an alternative energy source for electric vehicle batteries and apply design concepts to electric vehicles in Indonesia. The method applied is a qualitative approach with literature analysis and literature study. The research results show that in a comparative analysis of the use of solar thermal energy in electric cars with conventional vehicles that use fossil fuels, there is a significant difference in reducing carbon emissions. The results of the analysis also strengthen the argument about the superiority of electric cars in terms of environmental friendliness so that the design concept for implementing solar thermal energy in electric vehicles in Indonesia becomes very effective to implement.